2013
DOI: 10.1007/s11899-013-0163-4
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma in Pregnancy

Abstract: The peak incidence of Hodgkin lymphoma (HL) coincides with reproductive years, and as many as 3 % of all HL patients present with concurrent pregnancy. The management of a pregnant patient with HL requires a multidisciplinary approach combining expertise in medical oncology, high-risk obstetrics, and neonatology, as well as effective communication with the patient and her family. The goal is to optimize the mother’s chance of a cure while allowing for delivery of a healthy child. A pregnant patient with HL sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 32 publications
0
36
0
3
Order By: Relevance
“…Furthermore, inclusion of cases diagnosed before pregnancy or postpartum to the pooled sample of HL in pregnancy would also overestimate the true incidence. Recently, Bachanova and Connors reported that the largest clinical series of HL in pregnancy published in 1992, involved 48 women [4,17]. Our study is thereby important as it provides a large, unbiased population including 638 cases of HL in pregnancy with relatively stable incidence estimates over time.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, inclusion of cases diagnosed before pregnancy or postpartum to the pooled sample of HL in pregnancy would also overestimate the true incidence. Recently, Bachanova and Connors reported that the largest clinical series of HL in pregnancy published in 1992, involved 48 women [4,17]. Our study is thereby important as it provides a large, unbiased population including 638 cases of HL in pregnancy with relatively stable incidence estimates over time.…”
Section: Discussionmentioning
confidence: 92%
“…Hodgkin's lymphoma represents the most common hematological malignancy complicating pregnancy, which is a function of the increased incidence of HL in the reproductive period, 15-34 years of age [4,7]. Smith et al also used the ICD-9 coding system to characterize the occurrence rates and nature of outcomes for cancer-associated obstetric deliveries, and found that HL in pregnancy was amongst the five most predominant malignancies [1,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a reported incidence ranging from 1 per 1,000 to 1 per 6,000 deliveries. [2] Since it is one of the most curable forms of lymphoma so FNAC plays a very important role in quick diagnosis and effective treatment of such cases. Radiological investigations have their limitations in pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, about 3% of HL patients present with concurrent pregnancy. These patients are diagnosed with same-stage disease as non-pregnant patients [10]. NHL is more problematic in this regard as patients may be diagnosed at later stages because pregnancy may masquerade symptoms [11].…”
Section: Hematologic Malignanciesmentioning
confidence: 99%